2018
DOI: 10.3389/fpsyt.2018.00656
|View full text |Cite
|
Sign up to set email alerts
|

Autism, Joint Hypermobility-Related Disorders and Pain

Abstract: Autism Spectrum Disorder (ASD) and Joint Hypermobility-Related Disorders are blanket terms for two etiologically and clinically heterogeneous groups of pathologies that usually appears in childhood. These conditions are seen by different medical fields, such as psychiatry in the case of ASD, and musculoskeletal disciplines and genetics in the case of hypermobility-related disorders. Thus, a link between them is rarely established in clinical setting, despite a scarce but growing body of research suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 64 publications
2
61
0
Order By: Relevance
“…Higher pain severity in combination with increased interoceptive sensitivity may have additional emotional consequences such as anxiety and fear, which also may contribute to higher disability levels. Furthermore, recent studies showed the potential role of neurodiversity, such as Attention-deficit/hyperactivity disorder (ADHD) and Autism Spectrum Disorders (ASD) in G-HSD/hEDS [85,86]. The potential connection between these psychiatric disorders and G-HSD/hEDS can be useful in clinical practice since it allows to better identify patients with ASD or ADHD who may be vulnerable for disabling pain.…”
Section: Discussionmentioning
confidence: 99%
“…Higher pain severity in combination with increased interoceptive sensitivity may have additional emotional consequences such as anxiety and fear, which also may contribute to higher disability levels. Furthermore, recent studies showed the potential role of neurodiversity, such as Attention-deficit/hyperactivity disorder (ADHD) and Autism Spectrum Disorders (ASD) in G-HSD/hEDS [85,86]. The potential connection between these psychiatric disorders and G-HSD/hEDS can be useful in clinical practice since it allows to better identify patients with ASD or ADHD who may be vulnerable for disabling pain.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, how a CG works is challenging to describe. Therefore, the theoretical background justifying the use of CG in our population is speculative and based on: (1) the frequent co-occurrences between ASD and proprioceptive dysfunction [29,30,68] and ASD and joint hypermobility [44][45][46]; and (2) the existing clinical use of CGs in EDS [47,48]. Hypotheses regarding how CGs work include: (1) a better sensing of the limbs in space by stretching the skin.…”
Section: Problems Raised By the Use Of Cgs In Patients With Autismmentioning
confidence: 99%
“…Joint hypermobility and cutaneous hyper-elasticity are the two main criteria for hEDS. Recently, it has been associated with ASD [44][45][46]. The hEDS/ASD comorbidity could account for a deficit of proprioceptive inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Both ADHD and ASD are neurodevelopmental disorders, 9 , 11 which accounts for their similarities as well as for the differences among them. A recent study by Berenguer et al showed that children with ASD (ASD alone or in co-occurrence with ADHD) showed worse theory of mind skills than children with ADHD, while children with ADHD symptomatology (ADHD alone or with co-occurring ASD) had a more extensive profile of executive functions (EF) deficits than children with ASD only.…”
Section: Introductionmentioning
confidence: 99%